PELUANG ASEAN COMMUNITY MENYELESAIKAN MASALAH ROHINGYA - Fransiskus X. Gian Tue Mali (Kajian Asia Pasifik, 2017)
This article seeks to discuss and analyze the fate of Rohingyas who are stateless because of being denied as citizens of Myanmar. Even Bangladesh as a neighboring country which for nearly four decades received a quarter million Rohingyas, eventually refused Rohingyas migration. Likewise, some countries in Southeast Asia such as Thailand and Malaysia also refused their migration. Security, economic, social and political issues are the reasons why these countries reject the presence of this group. ASEAN as a regional group of Southeast Asian countries should then make the issue of Rohingya a priority issue. With the declaration of the ASEAN Community, this migration of Rohingyas will ultimately become a problem, either now or in the future. Therefore this article seeks to address and answer the opportunities of ASEAN Community in facing the issue of Rohingyas migration, also its role in helping to solve the problem up to the upstream conflict in Myanmar. The analysis of this article is done by literature study method. Data obtained from books, reports and other sources related to the problem is then analyzed through analytical descriptive approach. The conclusion of this article is that ASEAN (ASEAN Community) should take action to interfere in Myanmar's internal affairs so that the issue of human rights violation can be solved completely. Suggestion is given to ASEAN to be done immediately and to make regulation in order to influence Myanmar to pay more attention to the fate of the Rohingyas. Keywords: ASEAN, ASEAN Community, Rohingya Abstrak Artikel ini berusaha membahas dan menganalisis nasib kaum Rohingya yang mengalami status stateless karena ditolak diakui sebagai warga negara Myanmar. Bahkan Bangladesh sebagai negara tetangga yang selama hampir empat dekade menerima seperempat juta penduduk Rohingya, pada akhirnya menolak migrasi warga Rohingya. Begitupun sebagian negara di Asia Tenggara seperti Thailand dan Malaysia yang juga menolak migrasi warga Rohingya. Isu keamanan, ekonomi, sosial, dan politik menjadi alasan negara-negara tersebut menolak kehadiran kelompok ini. ASEAN sebagai lembaga kumpulan negara regional Asia Tenggara kemudian sudah sepatutnya menjadikan isu Rohingya sebagai masalah prioritas. Dengan dideklarasikannya Komunitas ASEAN, tentu migrasi warga Rohingya ini pada akhirnya akan menjadi masalah, entah saat ini atau di masa yang akan datang. Oleh karena itu artikel ini berusaha membahas dan menjawab peluang Komunitas ASEAN dalam menghadapi persoalan migrasi warga Rohingya, bahkan perannya dalam membantu penyelesaian masalah hingga ke hulu konflik di Myanmar. Analisis artikel ini dilakukan dengan metode studi pustaka. Data-data yang didapat dari buku-buku dan laporan-laporan serta sumber lain yang berkaitan dengan permasalahan tersebut kemudian dianalisis dengan pendekatan deskriptif analitik. Kesimpulan dari artikel ini bahwa sudah seharusnya ASEAN (Komunitas ASEAN) melakukan tindakan yang bisa dikatakan mengintervensi persoalan internal Myanmar agar persoalan pelanggaran HAM ini dapat diatasi sepenuhnya. Saran diberikan kepada ASEAN agar secepatnya dilakukan tindakan dan menyusun regulasi untuk dapat memengaruhi Myanmar agar lebih memperhatikan nasib kaum Rohingya. Kata kunci: ASEAN, Komunitas ASEAN, Rohingya